Investigating the Effect of Delamination Size, Stacking Sequences and Boundary Conditions on The Vibration Properties of Carbon Fiber Reinforced Polymer Composite - Imran,Muhammad (2019)
Abstract Composite structures are extensively used in various fields ranging from, but not limited to marine, aerospace, automotive, agricultural and industrial equipment due to their unique and excellent properties like weight associated with density. On an increase in their applications, it also requires special attention to manufacture and process the composites to acquire the high level of stability. Most critical defect in composite structures that have attracted many researchers is delamination. Delamination in composite structures are inevitable during service period. Present work is focused on investigating the effect of presence of delamination in the carbon fiber reinforced composite plate using finite element solver software, ANSYS. Present analysis will focus to find the effect of delamination size, boundary constraints and layups on the natural frequency of carbon fiber composite plate. Analytical results were also analyzed using MATLAB environment. Governing equations were derived using Rayleigh-Ritz method. The natural frequency reduced on an increase in delamination size and it is high in clamped-clamped boundary conditions rather than simply supported constraints. The finite element results are then compared with analytical results for clamped-clamped boundary conditions and found in close agreement.